A Case of Babesiosis in a Pregnant Patient Treated with Red Blood Cell Exchange Transfusion. (30th May 2019) - Abittan, Baruch; Nizam, Aaron; Oey, Michael; Callan, Felicia; Simmonds, Lisa; Pachtman, Sarah L.
Abstract : Babesiosis, caused predominantly by Babesia microti, is an emerging health risk in the Northeastern and Midwestern United States. We present a case of a pregnant woman with history of splenectomy diagnosed with babesiosis at 23 5/7 weeks of gestational age refractory to antimicrobial therapy. She underwent the first reported red blood cell exchange transfusion for babesiosis in pregnancy, at 24 4/7 weeks of gestational age, which resulted in resolution of parasitemia. She had a full term, uncomplicated cesarean delivery. Exchange transfusion is potentially a safe treatment option for severe babesiosis infection in pregnancy and should be considered when other methods are poorly tolerated or ineffective.